Measurement of prompt open-charm production cross sections in proton-proton collisions at √s = 13 TeV - Tumasyan, A. (2021)
The production cross sections for prompt open-charm mesons in proton-proton collisions at a center-of-mass energy of 13 TeV are reported. The measurement is performed using a data sample collected by the CMS experiment corresponding to an integrated luminosity of 29 nb−1. The differential production cross sections of the D∗±, D±, and D0(D ¯) mesons are presented in ranges of transverse momentum and pseudorapidity 4 < pT< 100 GeV and |η| < 2.1, respectively. The results are compared to several theoretical calculations and to previous measurements. [Figure not available: see fulltext.]